2009
DOI: 10.1074/jbc.c900002200
|View full text |Cite
|
Sign up to set email alerts
|

let-7 Overexpression Leads to an Increased Fraction of Cells in G2/M, Direct Down-regulation of Cdc34, and Stabilization of Wee1 Kinase in Primary Fibroblasts

Abstract: microRNAs play a critically important role in a wide array of biological processes including those implicated in cancer, neurodegenerative and metabolic disorders, and viral infection. Although we have begun to understand microRNA biogenesis and function, experimental demonstration of their functional effects and the molecular mechanisms by which they function remains a challenge. Members of the let-7/miR-98 family play a critical role in cell cycle control with respect to differentiation and tumorigenesis. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 23 publications
10
71
1
Order By: Relevance
“…In vitro overexpression of let-7b in melanoma cells downregulated the expression of cyclins D1, D3, A and cyclin-dependent kinase (Cdk) 4 (21). Let-7b overexpression leads to an increased fraction of cells in G2/M, direct downregulation of Cdc34, and stabilization of Wee-1 kinase in primary human fibroblasts (22). microRNAs may also desensitize stem cells to external signals, leading to cell cycle arrest in G1/S transition (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro overexpression of let-7b in melanoma cells downregulated the expression of cyclins D1, D3, A and cyclin-dependent kinase (Cdk) 4 (21). Let-7b overexpression leads to an increased fraction of cells in G2/M, direct downregulation of Cdc34, and stabilization of Wee-1 kinase in primary human fibroblasts (22). microRNAs may also desensitize stem cells to external signals, leading to cell cycle arrest in G1/S transition (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of Wee1 is regulated by the Skp1/cullin/F-box complex that polyubiquitinates Wee1 for proteasome-dependent degradation (Watanabe et al, 2004). let-7, an miRNA frequently downregulated in gastric cancer (Zhang et al, 2007a), has been shown to target CDC34, the ubiquitinconjugating enzyme of the Skp1/cullin/F-box complex in primary fibroblasts, and thereby promoting the half-life and expression of Wee1 protein (Legesse-Miller et al, 2009). Whether a similar regulatory mechanism exists in gastric cancer cells, however, requires further elucidation.…”
Section: Dysregulated Mirnas In Gastric Cancermentioning
confidence: 99%
“…It has been reported that LIN28A can bind to the terminal loops of the let-7 miRNA precursor, thereby blocking the processing of let-7 into its mature form (10, 11, 30 -39). In addition, several let-7 target genes, such as CCND1 (64), CCND2 (65), CCND3 (65), CCNA2 (64), CDK4 (64,65), CDC25A (65), and CDC34 (66), have been shown to function as regulators of the cell cycle. Therefore, we explored whether LIN28A could regulate the cell cycle in a let-7-dependent manner.…”
Section: Lin28a Promotes Cancer Cell Growth In Vitro and In Vivo-mentioning
confidence: 99%